2019
DOI: 10.5539/jas.v11n12p40
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity Test for Measurement of White Clover Seeds Vigor

Abstract: This study aimed to evaluate the physiological performance of white clover seed lots of different tegument colours, besides to analyses the electrical conductivity test methodology with different seeds number, water volume and soaking periods. The experiment was developed at the Seed Didactic Laboratory in the Agronomy College “Eliseu Maciel” at the Federal University of Pelotas, in Pelotas-RS, Brazil. White clover seeds were manually separate, composing four lots of different coloured seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Tao et al found that there was an advantage in using high-vigor CMV seeds to achieve better seedling emergence, whereas low-vigor seeds caused limited seedling emergence [18]. The selection of high-vigor seeds has also been proven to be helpful for seedling emergence in other forage legumes, such as alfalfa (Medicago sativa L.) [19], white clover (Trifolium repens L.) [20], and birdsfoot trefoil (Lotus corniculatus L.) [21]. Thus, more attention should be paid to seed-vigor testing for forage legumes.…”
Section: Introductionmentioning
confidence: 99%
“…Tao et al found that there was an advantage in using high-vigor CMV seeds to achieve better seedling emergence, whereas low-vigor seeds caused limited seedling emergence [18]. The selection of high-vigor seeds has also been proven to be helpful for seedling emergence in other forage legumes, such as alfalfa (Medicago sativa L.) [19], white clover (Trifolium repens L.) [20], and birdsfoot trefoil (Lotus corniculatus L.) [21]. Thus, more attention should be paid to seed-vigor testing for forage legumes.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, apesar desses testes terem apresentados resultados satisfatórios, alguns parâmetros devem ser considerados, pois podem afetar os resultados do teste e, para obter informações confiáveis, fatores como teor de umidade das sementes, volume de água de imersão, temperatura de hidratação, integridade das sementes, genótipo, período de embebição, entre outros, devem ser estudados (SANTOS et al, 2019;VASCONCELOS et al, 2019). Assim, as metodologias necessitam ser ajustadas e padronizadas para as espécies florestais nativas considerando suas particularidades, para que futuramente estas informações a respeito dos testes e espécies possam ser incorporadas no sistema de certificação de sementes de espécies florestais nativas para comercialização das mesmas com alta qualidade.…”
Section: Introductionunclassified